Eco-Compatible Green Synthesis of 1, 2-Disubstituted Benzimidazole Derivatives and Their In-Silico Studies in Designing of Anti-Malarial Potent Candidates (International Journal of Scientific Research in Science and Technology, 2026)
With the green approach, a novel and sustainable synthetic method for 1,2-disubstituted benzimidazole have been developed successfully using eco-compatible catalyst. In this report we have prepared 1, 2-disubstituted benzimidazole derivatives by double condensation between o-phenylenediamine (OPD) with various substituted benzaldehydes in presence of eco-compatible catalyst waste curd water under stirring at room temp. The employment of waste curd water for this reaction provides both as solvent as well as reaction medium with excellent yield of 81-90% within less reaction time and ease of workup process. In addition to eco-compatible green synthesis of benzimidazole derivatives, we extended their in-silico docking studies with PDB ID 1LDG using CB dock-2 web server. The green synthesized benzimidazole derivatives showed range of interactions with Gly27, Ser28, Gly29, Met 30, Asp53, Thr 97, Ala 98, Gly99, Phe 100, Thr 101, Lys102, Asn116, Val138, Thr139, Asn140 amino acids residues were predominately estimated with acceptable dock score. This exploration confirms the anti-malarial candidature of 1, 2-disubstituted benzimidazole derivatives.